F12‐46C/T polymorphism as modifier of the clinical phenotype of hereditary angioedema. Issue 12 (26th August 2015) - Speletas, M.; Szilágyi, Á.; Csuka, D.; Koutsostathis, N.; Psarros, F.; Moldovan, D.; Magerl, M.; Kompoti, M.; Varga, L.; Maurer, M.; Farkas, H.; Germenis, A. E.
Abstract: The factors influencing the heterogeneous clinical manifestation of hereditary angioedema due to C1‐INH deficiency (C1‐INH‐HAE) represent one of the oldest unsolved problems of the disease. Considering that factor XII (FXII) levels may affect bradykinin production, we investigated the contribution of the functional promoter polymorphism F12 ‐46C/T in disease phenotype. We studied 258 C1‐INH‐HAE patients from 113 European families, and we explored possible associations of F12 ‐46C/T with clinical features and the SERPING1 mutational status. Given that our cohort consisted of related subjects, we implemented generalized estimating equations (GEEs), an extension of the generalized linear model accounting for the within‐subject correlation. F12 ‐46C/T carriers exhibited a significantly delayed disease onset ( P < 0.001) and did not need long‐term treatment ( P = 0.02). In a GEE linear regression model, the presence of F12 ‐46C/T was significantly associated with a 7‐year delay in disease onset ( P < 0.0001) regardless of SERPING1 mutational status. It is concluded that F12 ‐46C/T carriage acts as an independent modifier of C1‐INH‐HAE severity.